Model wychowania w nauczaniu bł. Jana Pawła II - Mastalski, Janusz (Verbum Vitae, 2012)
Pedagogy held an important role in the teachings of John Paul II. In many texts and speeches, John Paul II considered the problems related to upbringing. He touched on great and disturbing issues, but at the same time reminded one of the pedagogy of the Master from Nazareth. Analyzing the teaching of John Paul II, it may be stated that his texts contain a very exact model of upbringing consisting of six pillars: Christocentrism, a coherent teleology leading to salvation, Christian axiology, environmental support for upbringing, self-upbringing and the pedagogy of rules.